Educational attainment in childhood cancer survivors: a meta-analysis. Issue 4 (10th October 2019) - Saatci, Defne; Thomas, Andrew; Botting, Beverley; Sutcliffe, Alastair G
Abstract : Objective: To assess differences across educational outcomes in survivors of childhood cancer (CCS) compared with peers. Design: Systematic review and meta-analysis of observational studies. Data sources and study selection: Medline, EMBASE, ERIC, CINAHL and PsycInfo from inception to 1st August 2018. Any peer reviewed, comparative study with a population of any survivor of childhood cancer, from high-economy countries, reporting outcomes on educational attainment, were selected. Results: 26 studies representing 28 434 CCS, 17 814 matched controls, 6582 siblings and six population studies from 11 high-income countries, which have similar access to education and years of mandatory schooling as reported by the Organisation for Economic Cooperation and Development, were included. CCS were more likely to remain at compulsory level (OR 1.36, 95% CI 1.26 to 1.43) and less likely to complete secondary (OR 0.93, 95% CI 0.87 to 1.0) and tertiary level education (OR 0.87, 95% CI 0.78 to 0.98). They were more likely to require special educational needs (OR 2.47, 95% CI 1.91 to 3.20). Subgroup analyses revealed that survivors, irrespective of central nervous system (CNS) involvement, were less likely to progress onto secondary level compared with cancer-free peers (OR 1.77. 95% CI 1.46 to 2.15; OR 1.19, 95% CI 1.00 to 1.42, respectively). This, however, changed at tertiary level where those with CNS involvement continued to perform worse (OR 0.61, 95% CI 0.55 to 0.68) but those without appeared to perform similarly to their peers (OR 1.12, 95% CI 1.0 to 1.25). Conclusions: Compared with controls, we have elucidated significant differences in educational attainment in survivors. This is sustained across different countries, making it an international issue. CNS involvement plays a key role in educational achievement. Clinicians, teachers and policymakers should be made aware of differences and consider advocating for early educational support for survivors.